Pengaruh Pemanfaatan Teknologi Informasi, Partisipasi Pemakai Sistem Informasi Akuntansi, Dan Kemampuan Teknik Pemakai Terhadap Efektivitas Sistem Informasi Akuntansi Di Koperasi Simpan Pinjam Se - Kecamatan Sukawati - Ni Kadek Dinda Artha Dharmayanti; Cokorda Gde Bayu Putra; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2023)
ABSTRACT This observation was carried out with the aim of uncovering the relationship or influence that is formed from the use of information technology, the participation of users of accounting information systems, and the technical skills of users on the effectiveness of accounting information systems for savings and loans in Sukawati District. 13 savings and loan cooperatives in Sukawati sub-district were designated as the study population with a sample size of 39 people who would later be analyzed using multiple linear regression techniques. in current observations it is revealed that the use of information technology can increase the effectiveness of the use of accounting information systems. in an effort to increase the effectiveness of the use of information systems, the cooperative must be able to make improvements to the user's involvement with the accounting information system, and the user's technical skills. In the future, this research is expected to be a basis for consideration by various parties who wish to increase the effectiveness of the use of information systems in companies through components that can influence it.